Welcome to Westonci.ca, the place where your questions are answered by a community of knowledgeable contributors. Discover in-depth solutions to your questions from a wide range of experts on our user-friendly Q&A platform. Connect with a community of professionals ready to provide precise solutions to your questions quickly and accurately.
Sagot :
Answer:
Step-by-step explanation:
1). Let the equation of the line is,
y = mx + b
Here, m = slope of the line
b = y-intercept
Slope of a line passing through two points,
m = [tex]\frac{y_2-y_1}{x_2-x_1}[/tex]
We take two points from the table given (-3, -19) and (0, -1)
m = [tex]\frac{-19+1}{-3-0}[/tex]
m = 6
y - intercept 'b' = -1 [For x = 0]
Therefore, equation of the line will be,
y = 6x - 1
2). Equation of a line passing through a point (x', y') is,
y - y' = m(x - x')
Slope of the line passing through two points [tex](x_1,y_1)[/tex] and [tex](x_2,y_2)[/tex] is,
m = [tex]\frac{y_2-y_1}{x_2-x_1}[/tex]
We take two points from the given table as (2, 12) and (3, 18).
Slope of the line passing through these points will be
m = [tex]\frac{18-12}{3-2}[/tex] = 6
Equation of the line passing through (2, 12) will be,
y - 12 = 6(x - 2)
y = 6x - 12 + 12
y = 6x
By using a graphing tool we can graph these lines representing the tables.
We appreciate your time on our site. Don't hesitate to return whenever you have more questions or need further clarification. We hope our answers were useful. Return anytime for more information and answers to any other questions you have. Thank you for using Westonci.ca. Come back for more in-depth answers to all your queries.